The Global Impact of the COVID-19 Pandemic on Individuals' and Couples' Sexuality - Eleuteri, Stefano; Alessi, Federica; Petruccelli, Filippo; Saladino, Valeria (Frontiers in Psychology, 2022)
The COVID-19 pandemic and its related restrictions significantly impacted individuals' health, wellbeing, and security. Isolation, limitation of movement, social distancing, and forced cohabiting have had a strong influence on all areas of people's lives as well as on their sexuality. Investigating how the COVID-19 outbreak and its consequences impacted people's sexuality was the primary aim of this review. Particularly, we focused on: (1) the variables associated with the improvement or the deterioration of individuals' and couples' lives during the pandemic; (2) the use of sex as a coping strategy; (3) the impact of COVID-19 outbreak on LGBT people. Results have shown that the worsening of sexual life seems to be related to couples' conflict, emotions and psychological difficulties, being female, being single or away from the partner, being a health care worker, and having children. Moreover, a detrimental effect on sexuality was associated with stress, forced cohabitation, routine, anxiety and worry about the job and the pandemic, feeling partner distance, being unhappy with their partner, and lack of privacy. On the other hand, improvements in sexuality were associated with living happily with a partner, being happy and satisfied with a partner, feeling less stressed and more bored, having more free time, having fewer recreation opportunities, and having minor workload. During the pandemic, there was an increase in using sex toys, pornography consumption, masturbating, and trying sexual experimentations. Among LGBT people, an increase was found in the number of casual sexual partners potentially due to the perceived lower likelihood of transmission through sex. Moreover, the increase in sexual activity may have represented a coping strategy to quarantine-related distress.